All-Fiber Multiplexing and Transmission of High-Order Circularly Polarized Orbital Angular Momentum Modes With Mode Selective Couplers - Junfeng Yang; Huanhuan Liu; Fufei Pang; Jianxiang Wen; Haoqiang Zheng; Lifei Chen; Xinyu He; Yana Shang; Na Chen; Yingchun Li; Tingyun Wang (IEEE Photonics Journal)
We have demonstrated an all-fiber high-order circularly polarized (CP) orbital angular momentum (OAM) modes (de)multiplexing system based on second-order mode selective couplers (SMSCs). Such SMSCs combining standard single mode fiber and ring core fiber (RCF) are fabricated by a fusing and pulling technique, in which the RCF supports second-order vector modes (HE31 and EH11). During a pulling process, the HE31 and EH11 modes could be excited along the coupling region through evanescent wave interaction. By adjusting the polarization states, the excited second-order modes are transformed into two sets of second-order CP OAM (CP-OAM±2) modes and then transmit along the RCF. The second-order CP-OAM±2 modes, carrying a 2.95-Gb/s orthogonal frequency division multiplexing signals filled with the 16-level quadrature amplitude modulation signals, are successfully (de)multiplexed and propagated over a 3.7-km RCF. The experimental investigations show that the developed system to multiplex and transmit CP-OAM±2 can achieve forward error correction threshold that the received optical power is larger than −13 dBm. The obtained results show that the OAM modes can be generated, (de)multiplexed, and effectively transmitted in the RCF with favorable performance by the designed SMSCs.